Elaboración de un manual sobre la estructura floral de catorce especies ornamentales, de importancia económica en los cantones de Latacunga y La Maná - Cajas Changoluisa, Yajaira Verónica (2014)
Flowers have many forms differing in the size, number and arrangement reproductive parts thereof, the importation of this organ appears that is where it originates player and fruits (seeds) thus preserving the species . The present work aims at the development of a digital manual floral morphology with 14 economically important species the cantons Latacunga and La Manna. The samples for the development of the manual were taken from different farms producing towns flowers above, they were selected in post harvest and totally random, took five copies of each….